Evaluation of Sago Bark Waste Compost Maturity and Stability - Effa Radika, Bidin (Universiti Malaysia Sarawak (UNIMAS), 2020)
Sago bark (SB) waste is a type of solid waste obtained from debarking process of sago palm and it is abundantly available in Sarawak. It is commonly discharged to nearby stream or left to degrade nearby sago mills causing environmental problem. There was a lack of knowledge of utilize SB waste into compost. Thus, this study is an effort to utilize SB waste into useful organic compost for improvement of soil quality, hence could minimize the amount sago waste. The aim of this study the physicochemical characteristics of SB compost for use as plant growth support. SB compost was prepared by mixing SB with chicken manure and empty fruit bunch (EFB) at ratio 6:3:1. The temperature was monitored daily before turned the mixture of the compost. Evaluation of compost maturity and stability were done via physicochemical characterization of the composts in terms of pH, elemental, functional groups and nutrient analyses. The effect of the compost usage as growth medium was assessed towards spinach (Ipomea aquatica) via seed germination and pot study. Results showed that the temperature of SB compost reached the maximal range of 40 oC at the intermediate stage (90 and 120 days) and decreased to constant temperature at the final stage (180 days). The composts color was dark brown with earthy smell after 180 days composting. The pH of the SB compost is in the basic state. Mass loss of SB compost was 60.65%. The highest total ash content reached 61.64% at 120 days of composting. Total organic carbon decreased and reached the lowest value at 120 days with 10.20%. The C/N ratio was also decreased to 21.5% upon completing 180 days of composting process. The phosphorus content was increased when the composting duration increased and generating maximum concentration at 2.81 mg/L during the final stage of composting. K was found to be the highest amount of macronutrients in SB compost, while Zn was found to be the lowest among other macronutrients and micronutrients. The germination index (GI) for the studied vegetables was above 100%, while pot study showed that vegetables in compost media has higher growth compared to the control, after two weeks. SB waste are renewable waste that can be used as compost to improve the soil quality. Increasing the composting period resulted in better quality of SB compost in terms of maturity and stability.